The Impact of Transformational Leadership on Employee Satisfaction, Employee Performance, and Employee Engagement: The Insurance and Pension Fund Service - Mala Alfiyah Ningsih; Yoka Krisma Wijaya; Sidra Muntahari; Nur Damayanti (Politeknik Negeri Bandung, 2023)
Leadership style is a complex phenomenon involving the leader, followers, and circumstances. The leadership style in an organization is also related to the overall success of the team. This study intends to determine whether transformational leadership carried out by a company has a significant positive impact on the outcomes felt by employees in the insurance and pension fund service cluster of State Owned Enterprises (SOEs). This study utilized Partial Least Square (PLS) in SmartPLS 3.0 with a sample of 372 employees from class 3 and class 4 SOEs in the insurance and pension fund service cluster of SOEs. The results reveal that transformational leadership significantly impacts the outcomes felt by employees (in terms of employee satisfaction, employee performance, and employee engagement). This study confirms the positive relationship between one type of leadership and employee satisfaction, employee performance, and employee engagement in the insurance and pension fund service cluster of SOEs. This study proposes new insights and theoretical as well as managerial implications. Future research can consider other variables that can give a significant positive influence on the outcomes felt by employees, for instance working environment.